2016
DOI: 10.1097/fpc.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Val/Val glutathione-S-transferase P1 polymorphism predicts nonresponders in psoriasis patients treated with fumaric acid esters

Abstract: Fumaric acid esters (FAE) are beneficial in the treatment of psoriasis. However, about a third of psoriasis patients do not respond to FAE. We aimed to determine whether glutathione-S-transferase (GST) M1 and GSTP1 polymorphisms are associated with treatment outcome in psoriasis patients treated with FAE. We studied 84 psoriasis patients who were treated with FAE for 3 months. FAE nonresponders were defined as having psoriasis area and severity improvement index less than 50% after 3-month therapy. GSTM1 genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In detail, Gambichler et al investigated the role of glutathione-S-transferase (GST) M1 and GSTP1 polymorphisms in response to 3 month-treatment with DMF in 84 psoriasis patients. 40 They found out that the Val/Val GSTP1 polymorphism increased by 43 folds the risk of treatment failure (non-responders), while no association was reported for GSTM1. 40 Hence, the Val/Val GSTP1 polymorphism may be employed to screen for responders versus non-responders to DMT in the therapy decision process.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…In detail, Gambichler et al investigated the role of glutathione-S-transferase (GST) M1 and GSTP1 polymorphisms in response to 3 month-treatment with DMF in 84 psoriasis patients. 40 They found out that the Val/Val GSTP1 polymorphism increased by 43 folds the risk of treatment failure (non-responders), while no association was reported for GSTM1. 40 Hence, the Val/Val GSTP1 polymorphism may be employed to screen for responders versus non-responders to DMT in the therapy decision process.…”
Section: Methodsmentioning
confidence: 98%
“… 39 At a molecular level, the immunomodulation derives from cellular glutathione depletion (and the induction of glutathione-S-transferase) and oxidative stress. 40 This drug showed a good efficacy and tolerable safety profile. 39 The most common AEs (flushing and gastrointestinal disorders) occurred mainly during the first few weeks of treatment and tended to improve or resolve over time.…”
Section: Methodsmentioning
confidence: 99%
“… 16 DMF can easily enter cells as it is a highly lipophilic substance. 17 However, once DMF releases from its capsule (as a drug), it undergoes rapid pre-systemic hydrolysis with the help of ubiquitously-found esterases in GI tract, tissues, and blood. 18 , 19 The resulting active metabolite is monomethyl fumarate (MMF).…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione S-transferases (GSTs) [GSTs are detoxification agents that are used as catalyzers to conjugate the reduced form of glutathione (GSH) to xenobiotic substrates] which are induced by DMF, were investigated in psoriasis and it has been observed that Val/Val GSTP1 polymorphism is associated with non-responsiveness to treatment with this FAEs. 17 This polymorphism has also been suggested as a potential biomarker predicting the status of responsiveness to DMF in other diseases. 17 There is no information about the impact of GBM heterogeneity on response to DMF therapy and comprehensive studies on this field are required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation